Notes on a predation event of Passer domesticus (Birds, Passeridae) by Philodryas olfersii (Squamata, Dipsadidae) in an urban area of the Zona da Mata of Pernambuco, Brazil - Almeida, Gleymerson Vieira Lima de; dos Santos, Ednilza Maranhão (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
This communication reports a predation event, where the snake Philodryas olfersii captures and eats a House Sparrow Passer domesticus. This observation occurred in an urban area of the Zona da Mata, Pernambuco State, Brazil, in the municipality of Nazaré da Mata on June 21, 2009.